Producing Producers: Women and Electronic/Dance Music - Farrugia, Rebekah; Swiss, Thom (Current Musicology, 2008)
With interviews as the primary source material, this article illustrates the processes by which commonplace discursive and material practices situate women outside of the production of electronic/dance music (E/DM) in San Francisco. Because women’s efforts in E/DM production are in their infancy, this study is more concerned with the barriers women are experiencing than the strategies they are using succeed. Nonetheless, our interviews with women who are in the early phases of producing E/DM suggested the importance of strategies including networking with male producers, and working to undo a lifetime of exposure to the gendered discourses that circulate in popular culture, social contexts, and educational environments.